Missing women in the United Kingdom - Adamos Adamou; Christina Drakos; Sriya Iyer (IZA Journal of Migration, 2013)
This paper investigates the gender-selection decisions of immigrants in the United Kingdom, using data from the 1971-2006 General Household Survey. We examine sex-selection in the UK among immigrant families and the gender composition of previous births, conditional on socio-economic characteristics. Our key result is that better-educated immigrants balance their family after the birth of two sons, by having a daughter thereafter. Our study also is the first to estimate the number of missing women among Asian immigrants in a European country, contributing to research on the US and Canada that missing women are also a phenomenon of the developed world.
Keywords: J13; J15; O52; Z1; 330; sex-selection; gender bias; UK